Analisis Potensi Likuifaksi Berdasarkan Data Cone Penetration Test Dengan Metode Shibata Dan Teparaksa (Studi Kasus: Sekolah Al-Azhar Pekanbaru) - Herawati, Fitri; Yusa, Muhamad; Putra, Agus Ika (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Liquefaction is a condition where the ground loses the shear strength because increased pore water effect from cyclic loads (earthquake loads) very quickly and in a moment. The influence of soil characteristics, Cyclic Stress Ratio (CSR), Cyclic Resistance Ratio (CRR), Factor of Safety (FS), Liquefaction Potential Index (LPI), and settlement soil are crucial to determine the potential liquefaction.The liquefaction analysis using Cone Penetration Test (CPT) data has developed, namely from a mechanical sondir (CPTm) developed into an electrical sondir (CPTe). The calculation method used is the Shibata and Teparaksa Method (1988). The purpose of this research to compare the potential liquefaction based on the results of CPTm and CPTm which was converted to CPTe. This research data is secondary data for the results of CPTm testing taken from the results of soil testing at the time of the construction of the AlAzhar Pekanbaru School Jl. Swakarya, Pekanbaru City. According to the analysis, it can be conclude a higher liquefaction potential is obtained when using CPTm data that has been converted (CPTe). As a results it shows that the Liquefaction Potential Index (LPI) calculated based on converted CPTm data (CPTe) is dominantly greater than the LPI value based on CPTm data with a LPIm / LPIe ratio <1. Keywords: Keywords : Liquefaction, LPI, Shibata and Teparaksa (1988), Electrical Sondir,Mechanical Sondir.